A Study of FTIR, Thermal Properties and Natural Weathering Test on NBRVirgin/Recycled with SBR Blends - Nik Noriman, Zulkepli; Hanafi, Ismail (Taylor & Francis, 2013)
Link to publisher’s homepage at http://www.tandfonline.com